A study on country of origin image towards the perception of brand equity among Malaysians / Mohd Naguib Ainuddin Kamalludin - Kamalludin, Mohd Naguib Ainuddin (Faculty of Business and Management, 2015)
The purpose for this research is to study the relationship between the countries of origin image towards the perception of brand equity of Malaysian. There were two independent variables which are macro country or origin image and micro country of origin image and one dependent variable which is the perception of brand equity. The respondents of the study were 200 Malaysian consumers that were being selected by using a non-probability sampling method, mall intercept. 200 questionnaires were given to collect the data. The data was then analyzed using frequency analysis, reliability analysis, correlation analysis and regression analysis. The findings of the study show that macro and micro country of origin image does in fact have significant relationship towards the perception of brand equity.